2008
DOI: 10.1002/term.105
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of an oesophagus acellular matrix tissue scaffold

Abstract: The oesophagus acellular matrix (EAM) tissue-scaffold has the potential to serve as the foundation for a tissue-engineered oesophagus for repair of ablative defects. Similar to all collagen-based biomaterials, the EAM is subject to enzymatic degradation in vivo. The introduction of exogenous crosslinks to collagen molecules via glutaraldehyde (Glu) is the most accepted method of stabilizing collagen biomaterials, but fixation with Glu incurs adverse effects. Genipin (Gp), a naturally occurring crosslinking age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 44 publications
1
39
0
5
Order By: Relevance
“…It also has been found to be an effective collagen cross-linking agent (16). In previous studies, genipin showed significantly lower cytotoxicity and inflammatory reaction than did glutaraldehyde (17)(18)(19), and there have been many trials to use genipin as a collagen cross-linking agent in tissue engineering fields (20)(21)(22)(23)(24).…”
mentioning
confidence: 96%
“…It also has been found to be an effective collagen cross-linking agent (16). In previous studies, genipin showed significantly lower cytotoxicity and inflammatory reaction than did glutaraldehyde (17)(18)(19), and there have been many trials to use genipin as a collagen cross-linking agent in tissue engineering fields (20)(21)(22)(23)(24).…”
mentioning
confidence: 96%
“…However, use of these enzymes in cultured tissue mimics is expensive. Chemical agents like glutaraledehyde (GA) have been widely used to stabilize collagenous matrices (Sung et al, 1999b); yet, toxicity is a real concern (Bhrany et al, 2008;Chang et al, 2002;Sung et al, 1999a). Irradiation with ultraviolet (UV) light has been used to crosslink collagen (Cornwell et al, 2007;Dong et al, 2005;Menter et al, 2001), but it has limited use to crosslink cellular tissues and tissue equivalents because of the potential of UV-mediated DNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…[74,75]. Les MD sont donc extrêmement employées dans l'ingénierie tissulaire vasculaire, valvulaire cardiaque, cutanée, et urologique [76].…”
Section: Méthodesunclassified
“…La même équipe a par la suite stabilisé leurs scaffolds par « cross-linking » avec du glutaraldéhyde ou de la génipine afin de leurs conférer des forces mécaniques satisfaisantes. Le glutaraldéhyde engendrait une toxicité cellulaire non retrouvée avec la génipine [83]. Les DM oesophagiens permettent également la croissance de tissus musculaires lisses.…”
Section: Méthodesunclassified
See 1 more Smart Citation